Türk ceza hukukunda müsadere (TCK m. 54-55) - Baytaz, Abdullah Batuhan (My University, 2009)
saderesi, Kazanç Müsaderesi, Türk Ceza Kanunu madde 54 ve 55. ÖZET Müsadere, mülkiyet hakkını önemli ölçüde sınırlayan ve kanunda öngörülen koşulların gerçekleşmesi halinde, suç ile alakalı eşya veya kazancın sahibinden alınarak devletin mülkiyetine geçirilmesidir. Bu yaptırım, 5237 sayılı Türk Ceza Kanununun 54 ve 55. maddelerinde eşya ve kazanç müsaderesi olarak düzenlenmiştir. 765 sayılı Türk Ceza Kanununa göre daha kapsamlı olarak düzenlenen müsadere yaptırımı, güvenlik tedbiri olarak kabul edilmesinin yanında, eşdeğer müsadere, orantılılık ilkesi, kısmi müsadere, ortak mülkiyet halinde müsadere ve kaim değerin müsaderesi düzenlemeleriyle suçlulukla mücadelede etkin bir yaptırım halini almıştır. Çalışmamız, müsaderenin tanımının, tarihçesinin, çeşitlerinin, bu yaptırımın hukuki niteliğine ilişkin tartışmalar ile mukayeseli hukukta ve uluslararası sözleşmelerde müsaderenin anlatıldığı hukukunda müsadere yaptırımının anlatıldığı ikinci bölüm, müsadere usulü ve infazının anlatıldığı üçüncü bölümden oluşmaktadır. Goods Confiscation, Proceeds Confiscation, Turkish Penal Code Article 54 and 55

Confiscation, which is significantly limited to property right, can be describe as, if the conditions, which are prescribed by law, fulfilled, the things or proceeds, which are related with crime will be taken into the possession of the state. This sanction, which is called Goods Confiscation and Proceeds Confiscation, is regulated under Turkish Penal Code no 5237 article 54 and 55. Confiscation sanction under Turkish Criminal Code no 5237 is regulated more comprehensive than Turkish Criminal Code no 765. There are too many differences between codes of no 5237 and no 765. Acceptance of legal attribute of confiscation as a security precaution is the most important innovation. Furthermore, confiscation sanction is become more active at the fight against crime with the regulation of equivalent confiscation, proportionality principle, partial confiscation, in the case of joint ownership confiscation and replacement value confiscation. In our dissertation, we study about “Confiscation in Turkish Criminal Law”. In the first part of our dissertation we study about definition of confiscation, confiscation history, types of confiscation, discussions about legal attribute of this sanction with confiscation sanction under comparative law and international agreements. In the second part of our dissertation, we study about confiscation sanction in Turkish Law and the third part of our dissertation, we study about confiscation procedure and execution of confiscation order.
Keywords: Ceza Hukuku; Hukuk; Hukuk_Türk Ceza Hukuku